THE LAW OF FINE IN GENDER RELATIONSHIPS ON TRADITIONAL INTERPRETATION OENDANG-OENDANG SIMBOER TJAHAJA IN TULUNG SELAPAN, OGAN KOMERING ILIR, SOUTH SUMATERA - Gayung Kasuma (LITERASI: Indonesian Journal of Humanities, 2013)
The presence of Simboer Tjahaja book for the residents in South Sumatra generally and in Ogan Komering Ilir in particular, is the answer of the experienced social phenomenon. Simboer Tjahaja is a series of conceptual and symbolic meaning resulted in consequences over inappropriate behaviours to both ethics and manners. The essence of life association in the book is not only served as formal law but as common habit and local identity either. Genealogically, it served also as both cultural morality roots and life concept of society. As the time goes by, after phenomenon traced in the District of Tulung Selapan it was revealed that there were many facts that been changed and oriented. The friction occurred in the perspective nowadays is related to the women motivation trapped in the centre of modernization, economic interests, and globalization. The friction over dende (fine) was done by the society for money (materials) objectives. The case revealed if there was a denunciating (crime by accusation) of the victim or third parties involved. Otherwise, then this dende (fine) would not be given.keywords: dende (fine), globalization, the customary law, modernization